PENGARUH PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN BERPIKIR KREATIF SISWA KELAS VII MTs SE KECAMATAN SUTERA - Sefrinal, Sefrinal (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This research originated from the low ability of mathematical problem solving and creative thinking of students of MTs se Kecamatan Sutera. This research is Quasy Experiment. The population in this research were students of class 1thMTs se Kecamatan Sutera. Techniques used in sampling is random sampling. Test use to see the ability of problem solving and creative thinking students. Data were analyzed using mean aquality test that t-test and U-test. These result indicate that (1) the ability of mathematical problem solving and creative thinking of the students taught by using open-ended approach was better than ability mathematical problem solving and creative thinking of the students who taught by using conventional learning. (2) the ability of mathematical problem solving and creative thinking of the students with high entering behavior by using open-ended approach was better than the ability of mathematical problem solving and creative thinking student high entering behavior with taught conventional learning. (3) the ability of mathematical problem solving and creative thinking of the student with low entering behavior by using open-ended approach was better than the ability of mathematical problem solving and creative thinking of student low entering behavior with taught conventional learning